UNDANG-UNDANG MINERBA UNTUK KEPENTINGAN RAKYAT ATAU PEMERINTAH ? - Rizal Akbar; Charissa Azha Rasyid; Muhammad Ikram Nur Fuady (Fakultas Syariah Institut Agama Islam Negeri Palu, 2021)
Mining is one of the productive sectors in Indonesia. Good management of mining products requires good regulation as well. This study aims to provide criticism and suggestions to policymakers related to regulations in the mining world. The research method used is normative research with a statutory approach. The study results show that the latest revision of Law Number 3 of 2020 concerning Minerals and Coal (UU Minerba) gives rise to pros and cons. In addition, the Minerba Law should provide an embodiment of partiality to the community, but the researchers found a strong gap in the conflict of interest and the violation of the principle of regional autonomy. Furthermore, research shows that more concrete implementing regulations are needed to implement the Minerba Law better. Therefore, the revision of the Minerba Law is a crucial matter for policymakers to carry out immediately.